البناء والتركيب في رواية "طيور التاجي" لإسماعيل فهد إسماعيل (Syntax and Structure in the Novel 'Tuyoor Al- Taji' By Ismail Fahad Ismail) - بنت أحمد الحاج عثمان, رحمة; سعد عبد الرحمن الملّا, إيمان (Journal of Islam in Asia (E-ISSN 2289-8077), 2021)
شاع في الدراسات الأدبية الحديثة استخدام مناهج النقد الحديثة المنطلقة من علوم اللسانيات والأسلوب للنقد والتحليل، في ضوء إشارات وتلميحات متفرقة للنقاد عن عجز البلاغة التقليدية للولوج إلى مواطن الفن في الأدب الحديث واستيعابها. وهذه دراسة نقدية لعمل أدبي حديث، تعتمد على الدرس البلاغي القديم أداة للنقد، ومعيارًا تستند إليه في حكمها وتقويمها للعمل الفنّي، فجاءت لتفنيد تلك الادعاءات، وتقديم نموذج لنقد عمل فني حديث بأدوات تقليدية كلاسيكية. في روايته "طيور التاجي"؛ يستخدم الروائي الكويتي إسماعيل فهد إسماعيل أساليب وصور بلاغية أبانتها هذه الدراسة وقدّمتها بالوصف والنقد والتحليل. تقوم الدراسة على عرض تقديمي وجيز للبلاغة العربية وفنونها، ثم تقديم نماذج من فصول متفرقة من الرواية فيها من الصور والأساليب البلاغية ما يدعو للتوقف عندها وعرضها وتحليلها. الكلمات المفتاحية: إسماعيل فهد إسماعيل، الرواية، البلاغة العربية، المعاني، البيان. Abstract In modern literary studies, the use of modern critical approaches based on the sciences of linguistics and style has become widespread, as tools and methods of criticism and analysis, in light of the separate indications and cues of critics about the inability of traditional rhetoric to penetrate and comprehend the areas of art in modern literature. This is a critical study of a modern literary work that relies on the classical rhetorical lesson as a tool for criticism, and a criterion on which it relies in its judgment and evaluation of the work of art. In his novel "Birds of Taji"; Kuwaiti novelist Ismail Fahd Ismail applies rhetorical methods and images to describe, critic and analyse. This study highlights and analyses how the different ways in which the classical Arabic rhetorical terminologies and styles were utilized and applied throughout the novel. Keywords: Ismail Fahad Ismail, Kuwaiti Novel, Arabic rhetoric, Alma'ani, Albayan.